Diagnostic value of core needle biopsy and fine‐needle aspiration in salivary gland lesions. (6th July 2015) - Novoa, Eva; Gürtler, Nicolas; Arnoux, André; Kraft, Marcel
ABSTRACT: Background: Core needle biopsy (CNB) has gained acceptance as a minimally invasive procedure in the head and neck. Nevertheless, many concerns arise regarding the value and safety of this method in the assessment of salivary gland lesions. Methods: This prospective study comprises 111 patients with a salivary gland lesion. The results of ultrasound‐guided CNB were compared with those of fine‐needle aspiration (FNA) in the 103 histologically verified cases. Results: CNB achieved a higher accuracy than FNA in identifying true neoplasms (98% vs 91%) and detecting malignancy (99% vs 87%), and was also superior to FNA providing a specific diagnosis (93% vs 74%). In both methods, no complications, such as bleeding, infection, nerve injury, or tumor‐cell seeding, occurred. Conclusion: CNB is a simple, safe, and highly accurate procedure, which should be considered as an additional diagnostic tool in the assessment of salivary gland lesions. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E346–E352, 2016